Renewal of Ijtihad in the Modern Era: Historical Background and Current Developments - Said Ahmad Sarhan Lubis (International Journal Reglement & Society (IJRS), 2022)
This research was conducted to find out the historical background of ijtihad and its development in the present. The research methodology used is an Normative research methodology with a historical approach. Ijtihad as one of the sources of Islamic law in the history of its development, has dynamics. When the Prophet SAW was still alive, ijtihad was still very limited and narrow, because revelation was still continuing to come down as an answer to the problems that arose. So, ijtihad does not need to be done. Ijtihad at the time of the Companions was done by directly looking at the Qur'an. The ulama in the tabi'in period were divided into large groups based on the form of their ijtihad methodology, ahl al-hadith representing the textualists in the Hijaz and ahl ar-ra'yiu representing the substantialists in Iraq. This writing also wants to know the different approaches to new thinking in Fiqh carried out by the sects of Secterianism, Literalism, Thufiism, Tabrir and Moderates. Then from this writing and research, it explains how the History of Modernism in Islamic Law applies and the form of renewal of ijtihad in Indonesia